Digital Forensic Legal Study in Proving Criminal Defamation Cases (Decision Study Number 8/PID.SUS/2021/PN MSH) - Maulana Putra; Risdalina Risdalina; Indra Kumalasari M (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The method used in this study is normative legal research, which focuses on analyzing legal issues by referring to applicable regulations related to the study of digital forensic law in proving defamation cases. This research is based on Decision Number 8/Pid.Sus/2021/PN Msh, which highlights the crucial role of digital forensics in revealing evidence and determining the defendant's accountability. In this case, the defendant, ALI TUAHAN, was accused of defamation through a Facebook post using the account "LIKENT LETWARU." Digital forensic experts provided evidence that the post violated Article 45A paragraph (2) in conjunction with Article 28 paragraph (2) of the ITE Law, which prohibits the intentional dissemination of information intended to incite hatred or hostility based on ethnicity, religion, race, and inter-group differences (SARA). The law carries a maximum penalty of six years' imprisonment and a fine of up to IDR 1,000,000,000.00. The court found that the defendant's post influenced public opinion and harmed the reputation of the Regent of Central Maluku and his family. As a result, the defendant was sentenced to two months’ imprisonment and required to pay court fees of IDR 2,000.00. This case highlights the growing importance of digital forensics in resolving social media-related criminal cases.